"She Starts Breakdancing, I Swear!": Metaphor, Framing, and Digital Pregnancy Discussions. (2nd July 2020) - Ho, Janet
ABSTRACT: In health communication metaphor studies, mental and terminal diseases are often the center of attention. Yet, one of the most important life stages especially for many women, pregnancy, has received little attention to date. This paper seeks to close the gap by investigating the use of metaphors in 411, 362 words of internet pregnancy discussions. In particular, it compares how forum contributors used metaphors to frame different gestational issues across the three trimesters of pregnancy. Using a corpus-assisted approach, we found that various types of metaphors, namely objectification, personification, violence, and constraint metaphors, performed different discursive roles in portraying such issues as fetal development, pregnancy discomforts, and birth-giving stages. While we demonstrated that metaphor is a staple tool for enhancing maternal–fetal attachment that empowers oneself and one's fellow pregnant mothers, we also proposed the new term "attachment personification" for the use of unconventional metaphor not merely to personify but, furthermore, to foreground the personification of fetal movement in the womb. We also found that the interaction of metaphors with humor and hyperbole conveyed the uniquely expectant attitude of pregnant women toward their pregnancy discomforts, which is worth further attention in health communication studies.